Variasi Jumlah Kromosom Planlet Taraxacum officinale Weber ex FH. Wigg Hasil Regenerasi in vitro dari Eksplan Akar, Helai Daun dan Tangkai Daun - Ermayanti, Tri Muji; Lestari, Indah; Salamah, Andi (Perhimpunan Biologi Indonesia, 2014)
Taraxacum officinale Weber ex F. H. Wigg. is a herbaceous medicinal plant species belonging family Asteraceasewhich has apomictic and poliploid characteristics. Multiplication of shoots using tissue culture was used to obtaindefine high quality seedlings, uniform, stable or free of diseases. However, changes in chromosome number canoccur in regenerated plants. The research aim was to determine the chromosome number of T. officinale plants regeneratedfrom culture in vitro using explants of roots, petioles and leaf blades. Therefore, selection of regenerantscan be done in order to find out transplants which have high yield of secondary metabolites. Analysis of chromosomenumber from root tips samples was conducted using 24 plantlets regenerated from root, 27 plantlets regeneratedfrom leaf blade, 21 plants regenerated from petiole and 102 roots of grown seeds using orcein squash method.The results showed that germinating seeds (control) and regenerated plants had variation in chromosome number.The range of chromosome numbers from regenerated plants were 2n=8-39, and cells with diploid number (2n = 2x= 16) was as most observed. The range numbers in germinated seeds were 2n=10-38, and cells with triploid number(2n = 3x = 24) was as most observed. This results proved that variation in numbers of chromosome was caused byapomixis and poliploid characteristics of the parent plant regenerated to their regenerants.Keywords : Taraxacum officinale. Weber ex F. H. Wigg, in vitro regeneration, variasi, chromosome